The Role of Pabbajja Training in Strengthening the Mental Balance of Buddhist Panditas in Banten Province - Pramono, Eko; Ismoyo, Tejo; Sutawan, Komang; Susanto, Susanto (Journal of Education, Religious, and Instructions (JoERI), 2024)
This study discusses the role of Pabbajja Training in strengthening the mental balance of Buddhist Panditas in Banten Province. The Pabbajja Training process is a spiritual journey that involves Vipassana meditation, understanding Buddhist teachings, daily discipline, and the application of ethical principles. Through Vipassana meditation, practitioners can wisely manage emotions and thoughts. A deep understanding of Buddhist teachings helps practitioners gain a broader perspective on life. Daily discipline provides a structure for the development of mental balance, while ethical and moral principles serve as the foundation for inner stability. This study concludes that Pabbajja Training significantly contributes to strengthening the mental balance and inner well-being of Buddhist Panditas in Banten Province. Keywords: Pabbajja Training, Mental Balance, Industrial Revolution 4.0 Era